Pt. Madan Mohan Malviya - MISHRA, VANDANA (THE PRIMARY TEACHER, 2015)
Born in Allahabad, in 1861, emerged a spark, was a man who challenged the mightiest empire in the world with an extreme force of his moral strength and the power of his rhetoric and eloquence. He stood to protect his country’s spiritual and intellectual heritage that would lift his country out of the darkness and lead it to the era of self-respect and modernity. He was a man with elevated ideals and supreme human values. He can be honestly marked as one of the brightest stars ever to shine in this universe. He loved his country with a fiery passion and served its people with great and selfless devotion. He wanted to inculcate a feeling of brotherhood and goodwill in every individual. In his lifetime, he had great achievements. He played multiple roles all over his lifetime like as an educationist, spiritual leader, politician, social reformer, patriot, legislator and a great human being. He was the founder of the Banaras Hindu University. On his 153rd birth anniversary, this great educationist and freedom fighter, was chosen for the Bharat Ratna award, the country’s highest civilian honour this year. This paper is a tribute to the great soul with a focus on some of his contributions. This paper includes significant parts of his life, works and education that prove him as a great educationist and one of the great men of the century.